Case report: Nocardia gipuzkoensis infection in an immunocompetent patient diagnosed by metagenomic next-generation sequencing and whole genome sequencing - Liu, Chengxin; Yang, Juhua; Huang, Huiting; Zhan, Shaofeng; Xia, Xintian (Frontiers in Immunology, 2022)
The infection of Nocardia gipuzkoensis is a relatively uncommon form of pulmonary nocardiosis seen in clinical patients. In general, nocardiosis tends to occur in patients with immune deficiency. Here, we report a 23-year-old female who was admitted to the hospital due to cough and sputum production over 10 years, diagnosed with bronchiectasis. The N. gipuzkoensis infection was identified by metagenomic next-generation sequencing and whole genome sequencing. Imipenem/cilastatin and compound sulfamethoxazole tablets were used to control the infection and the pulmonary inflammation subsided gradually.